Effects of morphology and pore size of mesoporous silicas on the efficiency of an immobilized enzyme. Issue 17 (8th March 2021) - Kuo, Ping-Chung; Lin, Zhi-Xun; Wu, Tzi-Yi; Hsu, Chun-Han; Lin, Hong-Ping; Wu, Tian-Shung
Abstract : Mesoporous silica films were used as supports with high loading capacity and enzyme activity. Abstract : An investigation is performed into the efficiency of the Streptomyces griseus HUT 6037 enzyme immobilized in three different mesoporous silicas, namely mesoporous silica film, mesocellular foam, and rod-like SBA-15. It is shown that for all three supports, the pH value changes the surface charge and charge density and hence determines the maximum loading capacity of the enzyme. The products of the enzyme hydrolytic reaction are analyzed by 1 H-NMR. The results show that among the three silica supports, the mesoporous silica film (with a channel length in the range of 60–100 nm) maximizes the accessibility of the immobilized enzyme. The loading capacity of the enzyme is up to 95% at pH 7 and the activity of the immobilized enzyme is maintained for more than 15 days when using a silica film support. The order of the activity of the enzyme immobilized in different mesoporous silica supports is: mesoporous silica film > mesocellular foam > rod-like SBA-15. Furthermore, the immobilized enzyme can be easily separated from the reaction solution via simple filtration or centrifugation methods and re-used for hydrolytic reaction as required.